DEMOCRATIZING INTELLIGENCE OVERSIGHT IN INDONESIA: CHALLENGES, REFORMS, AND COMPARATIVE INSIGHTS - Waroi, Muhammad Nur Abdul Latif Al (International Journal of Multidisciplinary Research and Literature, 2024)
This study examines the democratization of intelligence oversight in Indonesia, emphasizing the need for robust accountability frameworks within its intelligence sector. While established democracies employ comprehensive oversight structures that include legislative, judicial, and independent bodies, Indonesia's current framework remains underdeveloped, constrained by historical, political, and institutional factors. The study explores Indonesia's oversight mechanisms compared to models from mature democracies such as those in Denmark, the United States, and Germany, where parliamentary committees, independent agencies, and judicial reviews collectively ensure transparency and mitigate abuse of power. Findings reveal that Indonesia's primary oversight challenges stem from limited legislative authority, insufficient judicial engagement, and a need for more independent oversight bodies. Additionally, limited public participation, including civil society and media, further hinders transparency. To enhance democratic intelligence oversight, this paper suggests reforms, including establishing specialized oversight committees, independent review agencies, and judicial oversight protocols. Such measures are essential for protecting civil liberties, fostering public trust, and ensuring intelligence accountability within Indonesia's evolving democratic landscape. This research contributes to the global discourse on intelligence reform, highlighting strategies for emerging democracies to strengthen intelligence governance in response to modern security challenges